1992
DOI: 10.1161/01.str.23.7.995
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral plasminogen activator activity in spontaneously hypertensive stroke-prone rats.

Abstract: Background and Purpose:In the spontaneously hypertensive stroke-prone rat, it is unclear whether plasminogen activator plays a role in the development of stroke. The present study was undertaken to investigate brain levels of plasminogen activator activity in spontaneously hypertensive stroke-prone rats and Wistar-Kyoto rats.Methods: Plasminogen activator was purified from the brains of rats of both strains. The purification involved used ammonium sulfate precipitation, gel filtration, a zinc chelate-Sepharose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…MMPs and plasmin system potentially cooperate in matrix degradation, tissue damage & /remodelling. Note all studies concerning inflammatory markers were conducted in the presence of salt loading or an unknown diet initiated at six-weeks of age (22,(78)(79)(80)(81)(82)(83)(84)(85). NO, nitric oxide; PA, plasminogen activator; MMP, matrix metalloproteinase; SHRSP, spontaneously hypertensive stroke prone rat; WKY, Wistar Kyoto rats; MRI, magnetic resonance imaging.…”
Section: Mmp2mentioning
confidence: 99%
See 1 more Smart Citation
“…MMPs and plasmin system potentially cooperate in matrix degradation, tissue damage & /remodelling. Note all studies concerning inflammatory markers were conducted in the presence of salt loading or an unknown diet initiated at six-weeks of age (22,(78)(79)(80)(81)(82)(83)(84)(85). NO, nitric oxide; PA, plasminogen activator; MMP, matrix metalloproteinase; SHRSP, spontaneously hypertensive stroke prone rat; WKY, Wistar Kyoto rats; MRI, magnetic resonance imaging.…”
Section: Mmp2mentioning
confidence: 99%
“…SHRSP grew faster (93), but produced less than half the amount of tissue plasminogen activator as age-matched WKY rats (82). Unfortunately, this has not been investigated in cerebral vessels.…”
Section: Systematic Reviewsmentioning
confidence: 99%
“…The molecular weight of the plasminogen activator was 67 kDa, 44 kDa and 38 kDa in fraction I, and 67 kDa and 44 kDa in fraction 11, respectively. In the previous studies, the plasminogen activator in both rats was t-PA with the molecular weight of 72 kDa in brain tissue (Matsuo et al 1992), and was u-PA with the molecular weight of 43 kDa, and 37 kDa and t-PA with the molecular weight of 67 kDa in kidney tissue (Okada et al 1990). Furthermore, the liver tissues of Wistar rats were analysed for plasminogen activator activity and t-PA mRNA (Quax et al 1990).…”
Section: Discussionmentioning
confidence: 94%
“…The total plasminogen activator activity which was calculated as the sum of fractions I and I1 was about 1.5-fold higher in WKY than in SHRSP. By contrast, the plasminogen activator activity in the brain (Matsuo et al, 1992) and kidney (Okada et al 1990) tissues of SHRSP has been reported to be about 1.5-2.0-fold higher than that of WKY. Thus, the content of fibrinolytic activity differs with the tissue in WKY and SHRSP.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation